Pengaruh Model Edukasi terhadap Peningkatan Pengetahuan Masyarakat tentang Penyakit Ginjal Kronik - Vitarani Dwi Ananda Ningrum; Rahma Yuantari; Dian Medisa; Irwan Nuryana Kurniawan (PENGURUS BESAR IKATAN DOKTER INDONESIA (PB IDI), 2022)
Introduction: Chronic kidney disease (CKD) is a global health problem with consistently increasing prevalence and incidence, poor prognosis, and high cost. CKD ranks third in funding in Indonesia, reaching IDR 2.3 trillion/year in 2018. Integrated Guidance Post (Posbindu) program affiliated to PHC (Puskesmas) with community cadres has been launched as a community empowerment effort to suppress CKD incidence. This study aimed to strengthen the capacity of Posbindu cadres as the health driving force about CKD to encourage public awareness of CKD risk factors. Method: This quasi-experimental study with one group pretest-posttest design compared four education models for Posbindu cadres in four PHC in Yogyakarta to improve their knowledge of CKD. All education models used the smart module with models 3 and 4 explicitly involving health-worker collaboration. Model 1 used posters, model 2 used leaflets, while model 4 also used posters and leaflets. Knowledge of CKD was assessed through a previously-validated questionnaire with four knowledge domains. Result: All of the 86 cadres were women aged 43.7±8.6 years, mostly with at least high-school education and no risk factors for CKD predisposition. The results showed that model 4 significantly improved knowledge of CKD risk factors, symptoms and examination, and prevention behavior. Meanwhile, improvement in the last domain about CKD treatment was likely affected by model 3. Conclusion: This study confirmed health-worker collaboration’s significance in increasing public knowledge of CKD. Adding various printed education media effectively increased knowledge of CKD, particularly in cadres with higher educational attainment.